Men and the classroom : gender imbalances in teaching - Drudy, Sheelagh (London ; New York : Routledge, 2005)
"The teaching of young children has long been dominated by women. This global phenomenon is firmly rooted in issues relating to economic development, urbanisation, the position of women in society, cultural definitions of masculinity and the value of children and childcare. Yet, despite media scare stories and moral panics about the underachievement of boys, there are surprisingly few empirically supported answers to vital questions." "The authors of this ground-breaking book have undertaken the largest, most in-depth study ever carried out on this topic, assessing both teachers' and students' views on teaching. Radical change is inevitably called for in order to increase the proportion of men entering the primary teaching profession, but many short-term and more achievable strategies are also suggested here which could be implemented by policy makers and senior managers quickly and efficiently. Academics, students and researchers will find this a long overdue expose of one of the most critical issues facing the teaching profession today."--BOOK JACKET.
Table of contents
Includes bibliographical references (p. [173]-181) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Sex differences in education; Male elementary school teachers; Electronic books